2022
DOI: 10.1002/pbc.29688
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive outcomes in survivors of childhood acute lymphoblastic leukemia: Experience from a tertiary care center in India

Abstract: Background: Data of neurocognitive deficits in survivors of acute lymphoblastic leukemia (ALL) is scarce from low middle-income countries (LMICs), and is influenced by biological and cultural variations. The objective of this study was to assess the prevalence and spectrum of neurocognitive deficits in a cohort of survivors from India.Procedure: Seventy survivors of childhood ALL were evaluated for neurocognitive deficits by the Indian adaptation of Wechsler Intelligence Scale for Children -Fourth Edition (WIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…During hospitalization, children with leukemia face prolonged and painful treatment, multiple hospitalizations, and disruption of normal developmental experiences, which predispose them to poor social adjustment and induce abnormal emotional and behavioral problems. Studies have demonstrated that behavioral problems in children with leukemia are mainly characterized by disciplinary and neurotic behaviors [3], including social withdrawal, anxiety/depression, somatization, inattention, and hyperactivity [4][5][6]. Notably, previous studies have focused on the speci c manifestations of behavioral problems in children with leukemia; however, the key in uencing factors that differentiate the behavioral problems of children with leukemia from those of healthy children have not been thoroughly explored.…”
Section: Introductionmentioning
confidence: 99%
“…During hospitalization, children with leukemia face prolonged and painful treatment, multiple hospitalizations, and disruption of normal developmental experiences, which predispose them to poor social adjustment and induce abnormal emotional and behavioral problems. Studies have demonstrated that behavioral problems in children with leukemia are mainly characterized by disciplinary and neurotic behaviors [3], including social withdrawal, anxiety/depression, somatization, inattention, and hyperactivity [4][5][6]. Notably, previous studies have focused on the speci c manifestations of behavioral problems in children with leukemia; however, the key in uencing factors that differentiate the behavioral problems of children with leukemia from those of healthy children have not been thoroughly explored.…”
Section: Introductionmentioning
confidence: 99%
“…Acute lymphoblastic leukemia (ALL), as well as other types of childhood intracranial brain oncology, can result in decreased cognitive functions in children after treatment [ 30 ]. A meta-analysis of neurocognitive functioning in lymphoblastic leukemia survivors showed that patients with ALL scored significantly worse in full-scale IQ and verbal IQ tests.…”
Section: Introductionmentioning
confidence: 99%